When the Mnemonic Actors Become Storytellers. The Lore of the ‘Recovery’ in 1970s Poland - Ćwiek-Rogalska, Karolina (Acta Poloniae Historica, 2024)
The article examines the memoirs of Polish soldiers who settled in the lands that Poland acquired after the Second World War, the so-called Recovered Territories. The author argues that these memoirs reflect different forms of conveying the stories about the ‘recovery’, i.e. the acquisition of the formerly German lands by the Polish state in 1945. Depending on the historical and political context, as well as the personal and collective experiences of the settlers, she identifies its two main forms: myth and lore. The myth involves stories that are considered authoritative and obligatory, while lore is a type of storytelling that involves stories that are considered flexible and optional by the people who tell or listen to them. She further analyses how the myth of the ‘recovery’ subsequently transformed over time into lore from the immediate post-war period up to the 1970s.